Hanguana sitinurbayai (Hanguanaceae), a new species from mossy montane forest of Gunung Nyiut Penrissen, West Kalimantan, Indonesia - Randi, Agusti; Widodo, R.m. Wiwied; Adirahmanta, Sadtata N. (Phytotaxa, 2023)
A new montane Hanguana species is described here, it is the first species to be described from the highlands in the genus whereas all the previous species were described from the lowlands, particularly in the swampy areas. Full descriptions with photographs as well as notes on distribution, ecology and habitat, conservation status, and key to the genus in Borneo are provided in this paper.